The gender gap in mathematics achievement: Evidence from Italian data. (June 2017) - Contini, Dalit; Tommaso, Maria Laura Di; Mendolia, Silvia
Highlights: Gender differences in the STEM disciplines are widespread in most OECD countries. We investigate the gender gap in maths test scores in Italy. Girls systematically underperform boys, and the gap increases with children's age. Boys perform better than girls even when conditioning on prior scores. The gap is small at low percentiles of the test scores' distribution, but large at the top. Abstract: Gender differences in the STEM (Science Technology Engineering and Mathematics) disciplines are widespread in most OECD countries and mathematics is the only subject where girls tend to underperform with respect to boys. This paper analyses the gender gap in math test scores in Italy, which is one of the countries displaying the largest differential between boys and girls, according to the latest Programme for International Student Assessment (PISA). We use data from an Italian national level learning assessment, involving children in selected grades from second to tenth, and analyse the gender gap in mathematics test scores using OLS, school fixed effects, quantile regression, metric free and dynamic pseudo-panel models. Our results show that girls systematically underperform boys, even after controlling for an array of individual and family background characteristics. The average gender gap increases with children's age, is larger among top performing children, and girls keep losing ground relative to boys when progressing in the education system.